Integrating educational technology in the delivery of design-based courses at a technical teachers' college in Zimbabwe - Goredema, Rachel; Masina, Rumbidzayi; Chinengundu, Tawanda (INVOTEC, 2024)
Educational Technology became vital in the teaching and learning process, particularly during the Covid-19 era. However, a host of challenges associated with the integration of ET in the teaching and learning process were unearthed. This study sought to establish the extent to which Educational Technology was integrated into the teaching and learning of Design-based subjects at the diploma level during the COVID-19 pandemic and to explore strategies that can be adopted to improve the quality of teaching and learning in teacher education in times of crises. The study employed a qualitative approach methodology utilising a case study research design.  A sample of five lecturers and twenty students was purposively selected. Data were analysed thematically. Results revealed that lecturers have adequate content knowledge about the design-based subjects which they teach but do not have sufficient technological and pedagogical knowledge. The study recommends in-service training of lecturers to effectively use educational technology in teaching processes.